Sonar and underwater acoustics - Marage, Jean-Paul (ISTE., 2010)
Sonar and Underwater Acoustics brings together all the concepts necessary for designers and users of sonar systems. Unlike other books on this subject, which are often too specialized, this book is accessible to a wider audience. The first part focuses on the acoustic environment, antenna structures, and electric acoustic interface. The latter provides knowledge required to design, as well as the development and implementation of chain processes for an active sonar from the conditioning input to output processing. The reader will find a comprehensive range of all problems encountered in underw.